Effects of simulated hypo-gravity on lower limb kinematic and electromyographic variables during anti-gravitational treadmill walking - Malaya, Christopher A.; Parikh, Pranav J.; Smith, Dean L.; Riaz, Arshia; Chandrasekaran, Subhalakshmi; Layne, Charles S. (Frontiers in Physiology, 2023)
Introduction: This study investigated kinematic and EMG changes in gait across simulated gravitational unloading levels between 100% and 20% of normal body weight. This study sought to identify if each level of unloading elicited consistent changes – particular to that percentage of normal body weight – or if the changes seen with unloading could be influenced by the previous level(s) of unloading. Methods: 15 healthy adult participants (26.3±2.5 years; 53% female) walked in an Alter-G anti-gravity treadmill unloading system (mean speed: 1.49±0.37 mph) for 1 minute each at 100%, 80%, 60%, 40% and 20% of normal body weight, before loading back to 100% in reverse order. Lower-body kinematic data were captured by inertial measurement units, and EMG data were collected from the rectus femoris, biceps femoris, medial gastrocnemius, and anterior tibialis. Data were compared across like levels of load using repeated measures ANOVA and statistical parametric mapping. Difference waveforms for adjacent levels were created to examine the rate of change between different unloading levels. Results: This study found hip, knee, and ankle kinematics as well as activity in the rectus femoris, and medial gastrocnemius were significantly different at the same level of unloading, having arrived from a higher, or lower level of unloading. There were no significant changes in the kinematic difference waveforms, however the waveform representing the change in EMG between 100% and 80% load was significantly different from all other levels. Discussion: This study found that body weight unloading from 100% to 20% elicited distinct responses in the medial gastrocnemius, as well as partly in the rectus femoris. Hip, knee, and ankle kinematics were also affected differentially by loading and unloading, especially at 40% of normal body weight. These findings suggest the previous level of gravitational load is important to consider in determining kinematic and EMG responses to the current level during loading and unloading below standard g. Similarly, the rate of change in kinematics from 100% to 20% appears to be linear, while the rate of change in EMG was non-linear. This suggests that kinematic and EMG measures decouple with unloading and may react to unloading uniquely.